Determinação de tiocompostos por voltametria e coulometria em matrizes salinas - Trevisan, Joselito (2006)
The Laboratory of Support to Hemodialysis Clinics (LACHEM) has been investigating for many years the behaviour of many species in saline matrices as hemodialysis salts. In this work, the determination of the five thiocompounds related to agricultural defensives was investigated through electrochemical techniques in saline medium, based on the ionic forces present in saline concentrates used in Hemodialysis also in the sea water. The thiocompounds studied were thiotriazines ametryn, desmetryn, prometryn and terbutryn, which belong to the class of herbicides and the Ethylenethiourea (ETU), which is a degradation product in the class of Ethylenebisdithiocarbamate (EBDC). The high persistence of the triazines in the environment and the high levels of EBDC degradation products applied in crops as defensives, were the principal reason why these species were chosen. Moreover, another important reason is the fact the Brazilian legislation still do not requires the control of agrochemicals for fluids used in hemodialysis, perhaps for the small number of methodologies existent for this case. The electrochemical behaviour of these species was investigated by Voltammetry, Amperometry and Coulometry in aqueous samples of different ionic strenght. The preconcentration of analytes in columns and the diffusion through of the membranes of Teflon simulating the hemodialysis process were also investigated in this work. Constant-potential coulometry was used to compare the electrochemical behaviour of agrochemicals in relation to carbon vitreous reticulated (CVR) electrodes with Hg electrodeposition as well as with copper electrode after Hg electrodeposition, in an off line system. In an on line system, an electrochemical cell was built to determine these species by using a copper wire with Hg electrodeposited as a working electrode. The analytes preconcentration in columns of polystyrene (PS) was an alternative for the determination of the agrochemicals by coulometry, considering that through this technique was only possible to detect concentrations in levels of the mg L-1 of ETU and thiotriazines, utilizing mercury electrodes built with large superficial areas which produce the best results in electrolysis. In this work, electrolysis results lower than 100% were adopted to reduce the analysis time. For the amperometrics measure, an on-line system with CVR electrode was investigated in the determination of triazines. This system allowed the analysis with a high sensibility and fast. Analytical curves with concentrations from 1 μg L-1 were gotten using this system. In measures by Voltammetry were utilized Hg electrodes (HMDE) and Au to determine triazines and ETU in concentrations from 2 μg L-1. In this work, the ETU diffusion as also investigated through Teflon membranes, simulating the hemodialysis process. In this process, the diffusion cell is divided in two parts, the flow and the counterflow paths, where circulate the donor solution (saline solutions with different ionic strenght) and the adsorbent solution. The aim of this work was to evaluate the influence of saline medium in the diffusion of those species through the Teflon membrane. In the process of hemodialysis, the membranes utilized presented a bigger permeability than the Teflon s, in a way that this material was chosen as an indicator in a limit situation. The saline medium was responsible for increments of 1,5 to 2,5% in the analyte diffusion through of Teflon, in relation to pure water. However, significative differences in the diffusion taxes for saline medium with the ionic strenght investigated (corresponding to the hemodialysis fluids and sea water) were not observed. This work discusses the results obtained in electrochemical systems, comparing the analytes determinations to different electrodes utilized in aqueous and saline samples with different ionic strenght.